MEANINGFUL LEARNING DALAM PEMBELAJARAN MATEMATIKA - Diki Irmawan; Deni Efendi; Fitria Lestari (Hipotenusa Journal of Research Mathematics Education (HJRME), 2021)
In the learning process not every student succeeds through the learning process done in other words not every student can achieve the learning objectives as expected. This is due to abstract mathematical concepts. Many factors influence it, including intelligence, learning readiness, interests, motivation, teacher abilities, maturity, family, school and community. The purpose of this study is to know the meaningful influence of learning on students' math learning outcomes. This research uses descriptive quantitative methods. The population in this study is all grade VII students of SMPN 1 Katibung Lampung Selatan. The results of the hypothesis test using the t-test showed the influence of meaningful learning application on improving the results of mathematics learning students of grade VII SMPN 1 Katibung south lampung. Students who apply meaningful learning have a higher average math learning outcome than the average student learning outcomes that do not apply meaningful learning. Thus, the application of meaningful learning can improve students' math learning outcomes.